Novel methylated DNA markers accurately discriminate Lynch syndrome associated colorectal neoplasia - Ballester, Veroushka (Epigenomics, 2020)
AIM: Acquired molecular changes in Lynch syndrome (LS) colorectal tumors have been largely unstudied. We identified methylated DNA markers (MDMs) for discrimination of colorectal neoplasia in LS and determined if these MDMs were comparably discriminant in sporadic patients. PATIENTS & METHODS: For LS discovery, we evaluated DNA from 53 colorectal case and control tissues using next generation sequencing. For validation, blinded methylation-specific PCR assays to the selected MDMs were performed on 197 cases and controls. RESULTS: OPLAH was the most discriminant MDM with areas under the receiver operating characteristic curve ≥0.97 for colorectal neoplasia in LS and sporadic tissues. ALKBH5, was uniquely hypermethylated in LS neoplasms. CONCLUSION: Highly discriminant MDMs for colorectal neoplasia in LS were identified with potential use in screening and surveillance.